The Influence of Information Technology, Organizations and Government Regulations on Decision Support Systems - Suhada, Muhammad Dody; Ali, Hapzi (Dinasti Information and Technology, 2024)
The influence of information technology, organization and government regulation on decision support systems is a scientific article in literature research within the ESSB framework. The purpose of this article is to develop a hypothesis about the influence between variables, which will be used in further research. The object of research is in online libraries, Google Scholar, Mendeley and other online academic media. The research method uses library studies in the form of e-books and open access e-journals  Qualitative descriptive analysis. The results of this writing are: 1) Information Technology influences decision support systems. 2) Organizations influence decision support systems. and 3) Government regulations influence decision support systems.